Intelligent system for managing invasive species - Πλεξίδα, Μαρία (2017)
This thesis aims at creating a framework for administrating visual, spatial, meteorological and environmental data of various invasive species that appear in the region of the Aegean Sea and by using data mining techniques will predict their future population numbers.